2014
DOI: 10.1002/aic.14660
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation of HMF over Pt/C in a continuous flow reactor

Abstract: The three-phase hydrodeoxygenation reaction of 5-hydroxymethylfurfural (HMF) with H 2 was studied over a 10 wt % Pt/C catalyst using both batch and flow reactors, with ethanol, 1-propanol, and toluene solvents. The reaction is shown to be sequential, with HMF reacting first to furfuryl ethers and other partially hydrogenated products. These intermediate products then form dimethyl furan (DMF), which in turn reacts further to undesired products. Furfuryl ethers were found to react to DMF much faster than HMF, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 21 publications
3
71
0
Order By: Relevance
“…The fact that the D products form at the same space times for which DMF yields begin to decrease suggests that they are formed from DMF. The major D product observed with the Pt 6 Ni/C catalyst was 2-hexanone, the same major product formed on Pt catalysts [8,22], while with PtNi/C 2,5-hexandione was observed, which was also the primary product formed on Ni/C catalysts [8].…”
Section: Hydrodeoxygenation Of Hmf In a Continuous Flow Reactormentioning
confidence: 49%
See 4 more Smart Citations
“…The fact that the D products form at the same space times for which DMF yields begin to decrease suggests that they are formed from DMF. The major D product observed with the Pt 6 Ni/C catalyst was 2-hexanone, the same major product formed on Pt catalysts [8,22], while with PtNi/C 2,5-hexandione was observed, which was also the primary product formed on Ni/C catalysts [8].…”
Section: Hydrodeoxygenation Of Hmf In a Continuous Flow Reactormentioning
confidence: 49%
“…It is not likely that the higher yields are due to the increase in temperature. In addition to the fact that previous work indicated that selectivities are not very different between 100 and 200 °C [11,22], one would expect the reaction of DMF to over-hydrogenated products to increase with temperature. The maximum in the yield as a function of space time in Figure 6 is clearly less steep than that found for Pt 6 Ni/C and PtNi/C catalysts.…”
Section: Hydrodeoxygenation Of Hmf In a Continuous Flow Reactormentioning
confidence: 92%
See 3 more Smart Citations